Research on laser cladding repair and engineering аpplication of high-strength precipitation-hardening steel XM-25 - Tiancheng An; Berdnikova Olena; Haitao Wu (НТУ "ДП", 2025)
XM-25, a high-strength martensitic precipitation-hardening stainless steel used in steam turbine blades, suffers from water erosion. This study restores large XM-25 blades using DED laser cladding. Results show enhanced tensile strength (>1200 MPa), yield strength (>1050 MPa), microhardness (>415 HBW), reduced residual stress, and 95% higher fatigue limit. The cladding layer demonstrates effective precipitation strengthening with uniformly dispersed strengthening phase particles, confirming restoration effectiveness.
Keywords: Martensitic; Precipitation hardened; DED; Laser Cladding; Repaire